"The Might of My Own Hand Has Gotten Me This Wealth": Reflections on Wealth and Poverty in the Hebrew Bible and Today. (January 2019) - Kaminsky, Joel S.
The growing gap between the wealthiest and poorest members of society is a pressing social concern regularly invoked in discussions surrounding taxation, the minimum wage, and the social safety net. Advocates of particular positions at times reference various biblical passages. This essay examines several relevant themes and passages within the Hebrew Bible in order to explore ways the Bible might be brought into productive conversation with these contemporary issues.